A new process for the utilization of Antarctic krill - Ellingsen, Trond E.; Mohr, Viggo (Process Biochemistry, 1979)
Keywords: NARE 1976/77; Sørishavet; biokjemi; krill; lyskreps; marinbiologi; plankton

Antarktisk krill : deteksjon - fangst - anvendelse; teknisk / økonomisk analyse - Fiskerstrand, Rolf (Universitetet i Trondheim Norges tekniske høgskole, Institutt for skipsprosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; krill; zooplankton; økonomi

Norsk fangst av antarktisk krill : teknisk/økonomisk analyse - Fiskerstrand, Rolf (Norges fiskerihøgskole, Universitetet i Trondheim, Norges tekniske høgskole, Institutt for marin prosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; historie; hvalfangst; krill; pelagisk; zooplankton; økonomi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and icebergs - Gade, Herman G. (Journal of Physical Oceanography, 1979)
Steady-state conditions are assumed to exist everywhere in the case of melting of the underside of an infinite slab of ice floating in sea water. Basic transfer equations for heat and salt are established and solutions derived for the interior corresponding to given far field values of the temperature and salinity of the water. The solutions are discussed in the T-S diagram where the behavior is particularly simple. Determining parameters are the characteristic velocities ks/d and Ks/h, where ks and Ks are the molecular and turbulent diffusivities, respectively, of salt, d and h the thicknesses of the corresponding laminar and turbulent layers. Also the nonmelting/nonfreezing case is discussed and the determining parameter established. Application of the theory to the Ross Ice Shelf (Little America V) gives acceptable results with d = 2 × 10−3 m and Ks = 20 −30 × 10−4 m2 s−1. Analysis of the static stability of the melt water mixtures reveals that with ambient temperatures approaching 17°C, the stratification becomes unstable. Icebergs brought to tropical waters will cause melt water mixtures to intrude at subsurface levels. Finally, convection obtained in laboratory experiments with melting ice in sea water is reported to be in concordance with the theoretically derived stability criterion.
Keywords: Sørishavet; geofysikk; glasiologi; hydrologi; oseanografi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica) - Soevik, Torleif; Braekkan, Olaf R. (Journal of the Fisheries Research Board of Canada, 1979)
Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Key words: krill, red feed, deep sea prawn, fluoride.
Keywords: Sørishavet; biokjemi; forurensning; krill; marin biologi; miljøgifter; plankton

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis